Life cycle and environmental assessment of calcium looping (CaL) in solar thermochemical energy storage. (1st April 2022) - Colelli, G.; Chacartegui, R.; Ortiz, C.; Carro, A.; Arena, A.P.; Verda, V.
Highlights: Calcium looping thermochemical energy storage environmental impact. Daily and seasonal energy storage strategies are analysed. Energy storage with reduced equivalent carbon dioxide emissions. Energy payback time of 2.2 years and 2.5 years depending on the storage strategy. Abstract: Calcium looping is a promising thermochemical energy storage process to be integrated into concentrating solar power plants. This work develops for the first time a comprehensive life cycle assessment of the calcium looping integration in solar plants to assess the potential of the technology from an environmental perspective. Two representative integrations are analysed, representing daily (hot) and seasonal (cold) storage designs. Similar performance environmental impacts are observed in both, with slightly better results for the seasonal storage case due to the simplified energy storage integration. The results show the moderate environmental impact of calcium looping thermochemical energy storage technology, resulting in lower equivalent carbon dioxide emissions ( 24 kg/MWh) than other energy storage options such as molten salt-based solar facilities (40 kg/MWh). Plant construction involves a higher energy demand for the process, whilst the operation and maintenance on the plant represent a moderate impact due to the low environmental impact of limestone, the unique raw material of the process, and the lower water consumption compared to typical concentrating solar power plants. Besides, the energy required for the system is first time analysed, obtaining an energy payback time of 2.2 years and 2.5 years depending on the storage strategy design.